Contracting non-state providers for universal health coverage: learnings from Africa, Asia, and Eastern Europe - Krishna D. Rao; Ligia Paina; Marie-Gloriose Ingabire; Zubin C. Shroff (BMC, 2018)
Abstract Background Formal engagement with non-state providers (NSP) is an important strategy in many low-and-middle-income countries for extending coverage of publicly financed health services. The series of country studies reviewed in this paper - from Afghanistan, Bangladesh, Bosnia & Herzegovina, Ghana, South Africa, Tanzania and Uganda - provide a unique opportunity to understand the dynamics of NSP engagement in different contexts. Methods A standard template was developed and used to summarize the main findings from the country studies. The summaries were then organized according to emergent themes and a narrative built around these themes. Results Governments contracted NSPs for a variety of reasons - limited public sector capacity, inability of public sector services to reach certain populations or geographic areas, and the widespread presence of NSPs in the health sector. Underlying these reasons was a recognition that purchasing services from NSPs was necessary to increase coverage of health services. Yet, institutional NSPs faced many service delivery challenges. Like the public sector, institutional NSPs faced challenges in recruiting and retaining health workers, and ensuring service quality. Properly managing relationships between all actors involved was critical to contracting success and the role of NSPs as strategic partners in achieving national health goals. Further, the relationship between the central and lower administrative levels in contract management, as well as government stewardship capacity for monitoring contractual performance were vital for NSP performance. Conclusion For countries with a sizeable NSP sector, making full use of the available human and other resources by contracting NSPs and appropriately managing them, offers an important way for expanding coverage of publicly financed health services and moving towards universal health coverage.